ANALISIS DETERMINAN KEPUASAN WAJIB PAJAK DALAM MENGGUNAKAN LAYANAN E-FILLING PADA KPP PRATAMA SUMBAWA BESAR - Ragil Arisky; I Nyoman Sutama (Pusat Riset dan Publikasi, 2022)
This study aims to determine the factors that influence taxpayer satisfaction in using e-filling services at KPP Pratama Sumbawa Besar, including internal factors (X1) and external factors (X2) taxpayers. The type of this study is associative research. The number of samples in this study were 95 samples. Data collection using the questionnaire method. The data analysis used is multiple linear regression analysis techniques, partial and simultaneous hypothesis testing, and the coefficient of determination test (R2). The results showed that the internal and external factors of taxpayers had a positive and significant effect on taxpayer satisfaction in using e-filling services at KPP Pratama Sumbawa Besar, either partially or simultaneously. The value of the coefficient of determination (R2) is 0.957, which means that the ability of the internal and external factors of taxpayers to influencing variations in changes the taxpayer satisfaction in using e-filling services at KPP Pratama Sumbawa Besar is 95.7%, while the remaining 4.3% influenced by other variables outside of this study.